Blood Essential Trace Elements and Vitamins in Students with Different Physical Activity - Zaitseva, Irina P.; Skalny, Andrey A.; Tinkov, Alexey A.; Berezkina, Elena S.; Grabeklis, Andrei R.; Nikonorov, Alexandr A.; Skalny, Anatoly V. (Pakistan Journal of Nutrition, 2015)
The primary objective of the current investigation is to estimate the effect of different levels of physical activity on blood trace elements and vitamins concentration. A total of 97 students (55 male and 42 female) of P.G. Demidov Yaroslavl State University (Yaroslavl, Russia) took part in the current investigation. All the examinees gave their informed consent prior to the inclusion into the study. The female and male students were divided into the respective high, medium and low physical activity groups. Whole blood essential trace elements were assessed by inductively coupled plasma mass spectrometry using NexION 300D+NWR213 spectrometer. Quantitative estimation of water-and lipid-soluble vitamins was held using high-performance liquid chromatography at PerkinElmer S200. The results obtained indicate that blood trace elements’ levels do not change in response to physical activity in females. At the same time, blood copper, iron, magnesium and selenium concentrations in males are decreased along with elevated physical activity. Increased physical activity in females is associated with a non-significant decrease in blood ascorbic acid level, whereas a significant decrease in blood retinol concentrations was observed in males. It is notable that the maximal gender differences in blood vitamin and trace element values were observed in the high physical activity groups. The results indicate gender difference in trace element and vitamin balance in response to different levels of physical activity. The obtained data underline the necessity of trace element and vitamin homeostasis monitoring before mineral and vitamin supplementation.